Audiation in the high school choral classroom: utilizing solfege alongside various methods of teaching music - Holbert, Kara (My University, 2025)
The lessons demonstrated in this report are focused on implementing the idea of audiation within the context of a high school choral music classroom, utilizing solfege regularly alongside various methods of teaching as facilitators. In my classroom I noticed a general disconnect between visual and auditory learning. Students were often able to identify notes as they saw them, but they were unable to determine how those notes were supposed to sound. Because of this disconnect, I decided to create lessons that focused deliberately on the idea of audiation within the context of a regular rehearsal. My goal was to help the students in my class become well-rounded singers, combining their visual reading skills with their aural skills. Combining these aspects creates for much more efficient music-making and allows for students to become independent singers. Throughout these lessons, I utilized the curriculum I created for sight reading as part of my coursework in the Master’s program, as well as a variety of teaching methods I learned through many of my classes in the program. As a result of these lessons, I was able to see and hear growth in a relatively short amount of time. With deliberate attention to the idea of Audiation coupled with the utilization of solfege, as well as a variety of teaching methods, I was able to notice growth in desired skills in students that will ultimately make them stronger, well-rounded musicians. Over the course of my time in the Master’s program, I have been able to gain an incredible amount of new ideas, knowledge, skills, and methods. I have gained a much deeper understanding of effective music instruction, refining my own personal teaching philosophy along the way. Through my coursework, I developed a sight-reading curriculum specifically tailored to the needs of my students, with the goal of increasing overall literacy and independence in the choral music classroom. Leadership lessons from coursework also challenged me to consider the broader impact of my role as a music educator, encouraging me to lead with a broad vision, but also keep a student-centered mindset in every rehearsal. I was influenced by many different kinds of teaching methods, including Music Learning Theory, which emphasizes the concept of Audiation, which ultimately lead me to create this project. Audiation is a skill that I was taking for granted and needed to spend more time focusing on teaching the skill within my classroom. During the completion of this project, I was able to realize that Audiation was happening throughout my rehearsals, but students were not utilizing the skill when it was needed, or did not have the vocabulary to describe it. Deliberate attention to this concept, coupled with the sight-reading curriculum I created, and all of the various methods and philosophies I learned in the Master’s program have been showcased throughout this project. From this report I have gained tremendous insight about the direction I would like to grow in as a music educator, and how all of my coursework can lead me there.
Keywords: Audiation; Solfege; Choral music